2006
DOI: 10.1089/ten.2006.12.2171
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Fold Tissue Repairin VivoUsing a Synthetic Extracellular Matrix

Abstract: Chemically modified hyaluronic acid (HA)-gelatin hydrogels have been documented to support attachment, growth, and proliferation of fibroblasts in vitro and to facilitate repair and engineering of tissues in vivo. The objective of this study was to determine the optimal composition of a synthetic extracellular matrix (sECM) that would promote wound repair and induce tissue regeneration in a rabbit vocal fold wound healing model. The sECM was formed using a thiol-modified semisynthetic glycosaminoglycan (GAG) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
132
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 156 publications
(138 citation statements)
references
References 47 publications
2
132
1
3
Order By: Relevance
“…Its preparation protocol is very "user-friendly" and suitable for large-scale experimental protocols, its gelation time can be adjusted by varying pH or temperature, and its compliance can be altered by adjusting the degree of cross-linking [44]. In addition, its nature overcomes the issue of immunogenicity in in vivo applications [27][28][29][30][31][32][33]. In this study, the cellular morphology in 3-D encapsulated Extracel ™ was mostly rounded rather than the stretched, spindle-shape appearance seen in other scaffolds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its preparation protocol is very "user-friendly" and suitable for large-scale experimental protocols, its gelation time can be adjusted by varying pH or temperature, and its compliance can be altered by adjusting the degree of cross-linking [44]. In addition, its nature overcomes the issue of immunogenicity in in vivo applications [27][28][29][30][31][32][33]. In this study, the cellular morphology in 3-D encapsulated Extracel ™ was mostly rounded rather than the stretched, spindle-shape appearance seen in other scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…Another ECM equivalent, Extracel ™ , consists of a chemically modified hyaluronan (CMHA-S, also known as Carbylan ™ -S) and gelatin (Gtn-DTPH), which are co-cross-linked with polyethylene glycol diacrylate (PEGDA) [24,25]. This synthetic ECM (sECM) has been used successfully in numerous tissue engineering applications, has broad applicability in drug discovery [26], and is suitable for both 3-D and pseudo-3-D plating [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In ideal cases, injectable biomaterials are used to regenerate the extracellular matrix (ECM) in the LP and to restore the viscoelastic functions of the damaged VF tissue. [2][3][4] One challenge in designing VF-specific biomaterials is that their long-term functional outcomes are complicated by the phonation-induced biomechanical stimulation. In addition to the cell-biomaterial interactions that are pertinent to the chemical properties of the biomaterials, biomechanical stimulation also affects cell functions in VF growth and regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…28 The optimal sECM for both in vitro applications in 3D cell culture as well as in vivo applications in tissue repair has proven to be Carbylan TM -GSX 28 an sECM that is composed of thiolated gelatin and the thiolated biopolymer Carbylan TM -S. The efficacy of an injectable Carbylan TM -GSX hydrogel in restoring viscous and elastic moduli following scoop biopsy in rabbit vocal folds demonstrated that soft tissue repair was facilitated in vivo with this novel biomaterial. 29 We hypothesized that incorporation of growth factors and cytokines into Carbylan TM -GSX would further improve its tissue repair properties. We further hypothesized that this sECM could improve the rate and quality of repair in bone as well as in soft tissues.…”
Section: Introductionmentioning
confidence: 99%